Inequality and Mortgage Debts in Colombia - Guerrero-Pino, Yolanda (Iberoamerican Journal of Development Studies, 2016)
This article examines the impact of internal variables of the financial system (FS) regarding the economic inequality in Colombia during the 1993 through the 2010 period. It begins with the integration of two perspectives about the inequality induced by financial debts and the social responsibility of the FS. This investigation was done with an auto-regressive and distributed backwardness model, and a Granger Test. The results indicate that the economic inequality grows if the mortgage debt, the real estate dations as payment of debts, and the banking asset interest rates grow. Likewise, if the price of low status housing decreases, the economic inequality increases.
Keywords: economic inequality; mortgage debt; asset interest rates; price of low status housing